1999
DOI: 10.1093/carcin/20.9.1657
|View full text |Cite
|
Sign up to set email alerts
|

Selenium metabolism, selenoproteins and mechanisms of cancer prevention: complexities with thioredoxin reductase

Abstract: Numerous studies in animal models and more recent studies in humans have demonstrated cancer chemopreventive effects with Se. There is extensive evidence that monomethylated forms of Se are critical metabolites for chemopreventive effects of Se. Induction of apoptosis in transformed cells is an important chemopreventive mechanism. Apoptosis can be triggered by micromolar levels of monomethylated forms of Se independent of DNA damage and in cells having a null p53 phenotype. Cell cycle protein kinase cdk2 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
441
0
9

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 642 publications
(455 citation statements)
references
References 74 publications
5
441
0
9
Order By: Relevance
“…Given that anticarcinogenesis effects have been observed with mono-methylated forms of selenium (Ganther, 1999), only relying on selenoprotein saturation to determine threshold plasma selenium values for cancer prevention in humans may be an inappropriate approach. The implications of the relatively high proportion of subjects with plasma selenium less than 100 mg/l from a population health perspective is unclear at this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that anticarcinogenesis effects have been observed with mono-methylated forms of selenium (Ganther, 1999), only relying on selenoprotein saturation to determine threshold plasma selenium values for cancer prevention in humans may be an inappropriate approach. The implications of the relatively high proportion of subjects with plasma selenium less than 100 mg/l from a population health perspective is unclear at this time.…”
Section: Discussionmentioning
confidence: 99%
“…One significant limitation with plasma selenium threshold estimates, based on protein levels and activity, is that the positive health effects of selenium cannot be solely attributed to selenoproteins. There is considerable anticarcinogenesis evidence from mono-methylated forms of selenium (Ganther, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments, however, individual selenium compounds differed in their efficacy (Ip and Ganther, 1990;Ip, 1998). The protective effect of selenium is not readily explained in terms of prevention of oxidative DNA damage, since, as a rule, higher dosages of selenium than those optimizing peroxide metabolism are required (Combs et al, 1997;Combs and Gray, 1998;Ganther, 1999). Accordingly, topical discussions presume a direct antiproliferative effect of pharmacological selenium concentrations, be it due to enhancement of apoptosis by excess selenium supply or to distinct inhibition of proliferation-enabling enzymatic processes by certain selenium metabolites (Ganther, 1999).…”
Section: Selenium and Tumor Incidencementioning
confidence: 99%
“…Numerous studies have demonstrated cancer-chemopreventive effects of selenium in animals and more recently in humans [24,33,34]. Monomethylated forms of selenium (e.g.…”
Section: Biological Considerations: Triggering Zinc Release and Bindimentioning
confidence: 99%